Analysis of Seismic Vulnerability Index Based on Microtremor Signal Measurements in Balingka Agam Regency - Syarah Ramadhan (Department of Physics, Universitas Negeri Padang, 2026)
This study aims to analyze the seismic vulnerability index (Kg) in Nagari Balingka, Agam Regency, West Sumatra, which is located near the Sianok Segment. The Sianok segment is part of the active Sumatra Fault, making Balingka prone to seismic activity, especially earthquakes caused by fault segment movement. The method used is the Horizontal to Vertical Spectral Ratio (HVSR) based on microtremor signals. Microtremor signal recording was conducted at 16 measurement points scattered throughout Balingka. Microtremor signal recording data analyzed using the HVSR method will produce an H/V curve. The curve represents the dominant frequency value (f0) and amplification factor (A0) correlated with the seismic vulnerability index (Kg). The results of the microtremor analysis were used to create a map of the distribution of f0, A0, and Kg using QGIS software. The results of the study indicate that the dominant frequency values range from 1.9 to 14.75 Hz. Meanwhile, the amplification factor (A0) ranges from 1.7 to 5.79. Based on the dominant frequency (f0) and amplification factor (A0), the seismic vulnerability index (Kg) in Nagari Balingka ranges from 0.46 to 8.71.